The Limits of Pilgrimage Place - Rousseau, T. K. (Routledge Studies in Pilgrimage, Religious Travel and Tourism Ser., 2021)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Table of Contents -- List of figures -- 1. Place and porousness -- 2. The global dynamics of place and pilgrimage -- 3. Relics of the past and present -- 4. Heritage place, sacred place -- 5. Revelation and controversy at Medjugorje -- 6. Place and power -- 7. Making history at the House of Mary -- 8. The layers of the past -- 9. The limits of pilgrimage place -- Bibliography -- Index.